Sugestão de plano de gestão de resíduos sólidos para o município de Antônio Martins-RN - Rodrigues, Maria Kauana Mesquita (Universidade Federal Rural do Semi-Árido, 2019)
Population growth coupled with unbridled consumerism causes a significant increase in solid waste generation. But solid waste management is a complex issue, o it encompasses aspects: political, economic, social, cultural, environmental, among others. It was in this scenario that the law 12.305 / 10 was created putting into practice the National Policy of Solid Waste. This paper aims to make a diagnosis and propose a Solid Waste Management Plan for the municipality of Antônio Martins / RN. For the development of this work were carried out bibliographical and field research in the place under study, interviews with the secretary of urbanism and environment of the municipality, showing the consequences that the poor handling of waste can generate, also, the diagnosis, and the main techniques. Waste management, whose techniques are extremely relevant so that it is possible to properly package waste in a sustainable and efficient way for the benefit of society. However, it is necessary to rethink the solid waste management plan for the municipality, evaluating its insertion in the regional context, as well as scenarios and strategic perspectives for the area. It was looking for solutions to the current scenario that suggested measures such as selective collection and environmental education to solve them, because its implementation had positive results, o it expands and enables the opening of new markets, income, employment, and minimizing environmental impacts by improper disposal of waste, as well a social inclusion, to the extent that if waste is well relocated it will acquire commercial value. This study aims to contribute to the development of a Solid Waste Management Plan, as well as information related to the theme, highlighting the elaboration of a solid waste management plan in the municipality of Antônio Martins-RN.
Keywords: Resíduos; Diagnóstico; Coleta seletiva; Waste; Diagnosis; Selective collection; ENGENHARIAS::ENGENHARIA CIVIL